Organic anion-transporting polypeptide 2B1 knockout and humanized mice; insights into the handling of bilirubin and drugs - Wenlong Li; Dilek Iusuf; Rolf W. Sparidans; Els Wagenaar; Yaogeng Wang; Dirk R. de Waart; Margarida L.F. Martins; Stéphanie van Hoppe; Maria C. Lebre; Olaf van Tellingen; Jos H. Beijnen; Alfred H. Schinkel (Elsevier, 2023)
Organic anion transporting polypeptide 2B1 (OATP2B1/SLCO2B1) facilitates uptake transport of structurally diverse endogenous and exogenous compounds. To investigate the roles of OATP2B1 in physiology and pharmacology, we established and characterized Oatp2b1 knockout (single Slco2b1-/- and combination Slco1a/1b/2b1-/-) and humanized hepatic and intestinal OATP2B1 transgenic mouse models. While viable and fertile, these strains exhibited a modestly increased body weight. In males, unconjugated bilirubin levels were markedly reduced in Slco2b1-/- compared to wild-type mice, whereas bilirubin monoglucuronide levels were modestly increased in Slco1a/1b/2b1-/- compared to Slco1a/1b-/- mice. Single Slco2b1-/- mice showed no significant changes in oral pharmacokinetics of several tested drugs. However, markedly higher or lower plasma exposure of pravastatin and the erlotinib metabolite OSI-420, respectively, were found in Slco1a/1b/2b1-/- compared to Slco1a/1b-/- mice, while oral rosuvastatin and fluvastatin behaved similarly between the strains. In males, humanized OATP2B1 strains showed lower conjugated and unconjugated bilirubin levels than control Slco1a/1b/2b1-deficient mice. Moreover, hepatic expression of human OATP2B1 partially or completely rescued the impaired hepatic uptake of OSI-420, rosuvastatin, pravastatin, and fluvastatin in Slco1a/1b/2b1-/- mice, establishing an important role in hepatic uptake. Expression of human OATP2B1 in the intestine was basolateral and markedly reduced the oral availability of rosuvastatin and pravastatin, but not of OSI-420 and fluvastatin. Neither lack of Oatp2b1, nor overexpression of human OATP2B1 had any effect on fexofenadine oral pharmacokinetics. While these mouse models still have limitations for human translation, with additional work we expect they will provide powerful tools to further understand the physiological and pharmacological roles of OATP2B1.